PERAN GURU AKIDAH AKHLAK DALAM MEMBINA KARAKTER ISLAMI PESERTA DIDIK DI MADRASAH ALIYAH NEGERI BARITO SELATAN PLUS KETERAMPILAN - Jannah, Miftahul; Salim, Agus (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2024)
This study examines the Role of Aqidah Akhlak Teachers in Fostering Islamic Character of Students at Madrasah Aliyah Negeri Barito Selatan Plus Skills, Steps of Aqidah Akhlak Teachers in Fostering Islamic Character of Students at Madrasah Aliyah Negeri Barito Selatan Plus Skills and Factors that hinder and support in fostering the character of students at Madrasah Aliyah Negeri Barito Selatan Plus Skills. The role of Aqidah Akhlak teachers is an action taken by teachers to make students at Madrasah Aliyah Negeri Barito Selatan Plus Skills have good personalities. The research in this thesis uses a qualitative approach with a type of field research and is supported by references related to the theme discussed in this thesis. The sample of this study was 1 class with 28 students at Madrasah Aliyah Negeri Barito Selatan Plus Skills. The population in this study were teachers of the subject of aqidah akhlak who taught at Madrasah Aliyah Negeri Barito Selatan Plus Skills. To obtain field data, observation, interview, questionnaire and documentary techniques were used. The results of the study stated that the Role of Aqidah Akhlak Teachers in Fostering Islamic Character of Students at Madrasah Aliyah Negeri Barito Selatan Plus Skills is good. The steps of Aqidah Akhlak Teachers in Fostering Islamic Character of Students at Madrasah Aliyah Negeri Barito Selatan Plus Skills are good and the factors that hinder and support in fostering student character are background, teacher education, teaching time, teacher role models and the environment.